2019
DOI: 10.1038/s41598-019-52678-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined d-fagomine and omega-3 PUFAs on gut microbiota subpopulations and diabetes risk factors in rats fed a high-fat diet

Abstract: Food contains bioactive compounds that may prevent changes in gut microbiota associated with Westernized diets. The aim of this study is to explore the possible additive effects of d-fagomine and ω-3 PUFAs (EPA/DHA 1:1) on gut microbiota and related risk factors during early stages in the development of fat-induced pre-diabetes. Male Sprague Dawley (SD) rats were fed a standard diet, or a high-fat (HF) diet supplemented with d-fagomine, EPA/DHA 1:1, a combination of both, or neither, for 24 weeks. The variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 38 publications
4
25
0
Order By: Relevance
“…Because these parameters have been partially described and discussed in previous work [ 23 ], we include these data here as Supplementary Material (Figure S1 and Table S3) . All HF diet-fed groups presented a lower feed intake and higher energy intake than the STD group throughout the study.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Because these parameters have been partially described and discussed in previous work [ 23 ], we include these data here as Supplementary Material (Figure S1 and Table S3) . All HF diet-fed groups presented a lower feed intake and higher energy intake than the STD group throughout the study.…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that the combined supplementation with FG and ω-3 PUFA attenuates the increase in perigonadal adipose tissue content and the onset of insulin resistance induced by an HF diet [ 23 ]. The combination of ω-3 PUFA with another bioactive nutrient may be a useful nutritional strategy for the prevention of obesity and insulin resistance by enhancing anti-inflammatory and antioxidant status [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations